2008
DOI: 10.1007/s12031-008-9054-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of gLTP in Sympathetic Ganglia from Stress-hypertensive Rats: Molecular Evidence

Abstract: We previously reported behavioral and electrophysiological evidence indicating that superior cervical ganglia (SCG) from rats that developed hypertension as a result of chronic psychosocial stress expressed ganglionic long-term potentiation (gLTP) in vivo. In the present study, we present additional supportive evidence by measuring changes in protein levels of essential signaling molecules in ganglia from chronically stressed rats. We compared protein levels of essential, LTP-related signaling molecules in gan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 44 publications
3
10
0
Order By: Relevance
“…To examine if these changes also occur in ganglia from OZR, we measured the protein levels of signaling molecules by immunoblot analysis to compare basal levels in ganglia from OZR and LZR. The levels of many of these essential signaling molecules were similar to those detected in normal ganglia in which gLTP was evoked with HFS in vitro (Alzoubi et al 2008).…”
Section: Molecular Evidencesupporting
confidence: 58%
See 4 more Smart Citations
“…To examine if these changes also occur in ganglia from OZR, we measured the protein levels of signaling molecules by immunoblot analysis to compare basal levels in ganglia from OZR and LZR. The levels of many of these essential signaling molecules were similar to those detected in normal ganglia in which gLTP was evoked with HFS in vitro (Alzoubi et al 2008).…”
Section: Molecular Evidencesupporting
confidence: 58%
“…Recently, we have shown that in vitro HFS-induced gLTP is associated with an increase in the protein levels of key signaling molecules, including P-CaMKII, neural nitric oxide synthase (NOS-1) and PKC, and a decrease in calcineurin levels (Alzoubi et al 2008). Similar changes were observed in these signaling molecules in unstimulated ganglia from psychosocially stressed rats where gLTP had been expressed in vivo (Alkadhi et al 2005b;Alzoubi et al 2008).…”
Section: Molecular Evidencementioning
confidence: 70%
See 3 more Smart Citations